1999
DOI: 10.1098/rstb.1999.0431
|View full text |Cite
|
Sign up to set email alerts
|

The transmission dynamics of gonorrhoea: modelling the reported behaviour of infected patients from Newark, New Jersey

Abstract: A survey of the sexual behaviour of gonorrhoea patients in Newark was undertaken to evaluate parameters within a model of gonorrhoea transmission. Modelling work aimed to explain observed epidemiological patterns and to explore the potential impact of interventions. Reported behaviours, along with values derived from the literature, were used within a standard deterministic model of gonorrhoea transmission, where the population was stratified according to sex and rates of sex-partner change. The behaviours rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
129
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(136 citation statements)
references
References 36 publications
7
129
0
Order By: Relevance
“…We simulated epidemics for these two main classes of STD. To represent bacterial STDs, we drew parameter values from the literature on gonorrhoea, chlamydia and trichomoniasis Garnett et al 1999;Bowden & Garnett 2000): transmission rates are high, and infected individuals recover without immunity in roughly one month. To represent viral STDs, we chose parameters in the range appropriate for HIV and HSV-2 (Anderson et al 1989;Castillo-Chavez 1989;Mertz et al 1992;Blower et al 1998Blower et al , 2000: transmission is relatively slower, but there is no recovery.…”
Section: Validity Of Frequency-dependent Models Of Sexually Transmittmentioning
confidence: 99%
See 2 more Smart Citations
“…We simulated epidemics for these two main classes of STD. To represent bacterial STDs, we drew parameter values from the literature on gonorrhoea, chlamydia and trichomoniasis Garnett et al 1999;Bowden & Garnett 2000): transmission rates are high, and infected individuals recover without immunity in roughly one month. To represent viral STDs, we chose parameters in the range appropriate for HIV and HSV-2 (Anderson et al 1989;Castillo-Chavez 1989;Mertz et al 1992;Blower et al 1998Blower et al , 2000: transmission is relatively slower, but there is no recovery.…”
Section: Validity Of Frequency-dependent Models Of Sexually Transmittmentioning
confidence: 99%
“…The infection status of individuals (both human and animal) has been shown to affect their contact behaviour in STDs and other diseases (Kennedy et al 1987;Loehle 1995;Able 1996;Beckage 1997;Garnett et al 1999;Kiesecker et al 1999;Webster et al 2003), and evolutionary biologists have long speculated that parasites play a role in mating behaviour (Hamilton & Zuk 1982;Boots & Knell 2002). Proposed or observed mechanisms for lowered contact rates include debilitation and reduced vigour (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, individuals in such locales formed sexual partnerships with each other more frequently than would be expected by chance (Potterat et al 1985;Zenilman et al 1999), suggesting a pattern of 'assortative mixing' between members of core populations. However, when Garnett and colleagues applied a modified version of the model by Hethcote and Yorke to empirical data (Garnett et al 1999), the model suggested that, contrary to the assortative mixing observed in empirical studies, 'near-random mixing' was required to reproduce the observed distribution of gonorrhoea. In addition, Garnett's work suggested that their modelling approach had other limitations in that it was highly sensitive to assumptions on the parameters that describe gonococcal transmission, and as such was inadequate for testing interventions aimed at reducing gonococcal transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Information about parameter estimates for N. gonorrhoeae is scarce, so we chose to use non-informative priors for all parameters except the duration of infection which was informed by Garnett et al [25]. The ranges for the expected prevalence and incidence of diagnosed infections in HMW were based on the National Health and Nutrition Examination Survey [26] and surveillance data [27], both from CDC.…”
Section: Model Transmission Modelmentioning
confidence: 99%